Financial Literacy, Government Support, and Fund Management Effectiveness in Buddhist Religious Organizations - Franky Okto Bernando; Nico Pranata Mulya; Andhyka Wicaksono; Vallentina Febrianti Tri RS; Lusianna Lusianna (Faculty of Social Science, Universitas Negeri Padang, 2026)
Effective financial management is essential for the sustainability and accountability of religious nonprofit organizations. Financial literacy has been widely recognized as a key internal capability for strengthening financial governance. However, empirical evidence on the role of government support as a moderating factor remains inconclusive, particularly in underexplored religious contexts. This study examines the effect of financial literacy on fund management effectiveness in Buddhist religious organizations and investigates whether government support moderates this relationship. Using a quantitative explanatory design, data were collected through a structured questionnaire administered to 150 administrators of Buddhist religious organizations. The data were analyzed using multiple linear regression and moderated regression analysis. The results indicate that financial literacy has a positive and statistically significant effect on fund management effectiveness (beta = 0.445, p < 0.001), suggesting that higher financial competence among administrators leads to more effective financial planning, utilization, and reporting. However, government support does not significantly moderate the relationship between financial literacy and fund management effectiveness (beta = -0.001, p = 0.837). These findings demonstrate that internal financial capabilities play a more decisive role in determining fund management effectiveness than external institutional support. The study contributes to nonprofit governance literature by clarifying the boundary conditions of government support in religious nonprofit organizations. Practically, the findings suggest that strengthening financial literacy among religious organization administrators represents a more effective strategy for improving financial accountability than reliance on external support alone.